Implementation of Fish Pellet Production Using Palm Kernel Waste in Merangin Village, Kampar - Amraini, Said Zul (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
The community of Merangin Village, Kampar Regency, predominantly relies on fish farming for sustenance and has been facing notable challenges in cultivation, particularly concerning the costly factory-made pellets, which constitute a significant portion of production expenses. To address this, an alternative solution was autonomous fish pellet production using locally abundant palm kernel waste. Despite this, many community members lacked understanding of the production process and raw material processing. Through a community service program at the University of Riau, targeted technology transfer efforts aimed to empower residents to produce fish pellets independently. The program focused on enhancing knowledge through comprehensive guidance on pellet production. The implementation of this program was expected to enable Merangin Village residents to manufacture their own fish pellets, potentially enhancing income and fostering a sustainable fish farming venture. The implications of the program included optimized palm waste utilization, reduced production costs, increased income, and effective waste management. A locally designed fish pellet machine, boosting a production capacity of up to 50 kg/hour, facilitated community to control over production and reduced dependence on costly commercial options. The pellet formula integrated locally available ingredients such as bran, palm kernel cake, tofu dregs, fish waste, and kiambang. Educational campaigns and practical training sessions equipped fish farmers with the skills to operate the pellet machine, formulate recipes, and manage production effectively, thereby contributing to the socio-economic development of Merangin Village and other communities.